Neuroinflammation and spinal cord injury - Popovich, Phillip (Henry Stewart Talks, 2012)
The conflicting effects of Inflammation in the injured spinal cord, Progression of intraspinal bleeding, The cellular and molecular components of acute and chronic inflammation, The injurious and reparative effects on neurons and glia